u-3/4-2=3u/2+2u+1/5

Simple and best practice solution for u-3/4-2=3u/2+2u+1/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u-3/4-2=3u/2+2u+1/5 equation:


u-3/4-2=3u/2+2u+1/5

We simplify the equation to the form, which is simple to understand
u-3/4-2=3u/2+2u+1/5

Simplifying:
u-0.75-2=3u/2+2u+1/5

Simplifying:
u-0.75-2=+1.5u+2u+1/5

Simplifying:
u-0.75-2=+1.5u+2u + 0.2

We move all terms containing u to the left and all other terms to the right.
+1u-1.5u-2u=0.2 + 0.75+2

We simplify left and right side of the equation.
-2.5u=+2.95

We divide both sides of the equation by -2.5 to get u.
u=-1.18

See similar equations:

| -5x+(-20)=20 | | X/15=-11 | | 2/m-x/3=7/15 | | 2/4-x/3=7/15 | | -3(5-r)=9 | | 31.5=0.75X | | -3(x-1)=2-3x | | (16*(4x)^3)/x^2 | | 16^-2/(4a)^-3=x | | 35+(6+r)=85 | | 16^-2/(4a)^-3 | | 20x+220=500 | | 0.2(10000)-0.08y=0.02(y+10000) | | b+b+c+c= | | 12w^3+16w^4= | | 6e^2-5e-6=0 | | 6+7+1(n*5)=-12 | | 5x^2+x+7=0 | | U/4=6.5 | | 12a+12b+2c+6c-4b-4a= | | ((16x)/((x^2)+6))=0 | | -7g=1 | | 12m^2-8m-15=0 | | 16x/((x^2)+6)=0 | | 1m^2-8m-15=0 | | 5x+22(x-2)=307 | | 3x/5-8=-11 | | 14p+17q+p-6q-5p= | | x+2y-2=0 | | (x/3)+7=6 | | 5n+8n=3+2n | | -4+1=23 |

Equations solver categories